The Final Solution in Norway: Local Collaboration in the Holocaust - Bruland, Bjarte (Holocaust and genocide studies, 2023)
This article analyzes how German agencies and Norwegian collaborators together implemented the Final Solution in Norway. After the German invasion in April 1940, Hitler appointed Josef Terboven Reichskommissar of Norway. Initially, the German occupiers discreetly introduced anti-Jewish measures through local Norwegian agencies against the country’s approximately two thousand Jews. Until Fall 1942, no laws or decrees to exclude Jews from the majority population appeared, mainly because Terboven and his Norwegian collaborators feared that such measures could generate sympathy for the Jews. When, however, the resistance movement intensified, becoming more militarized, and a rare logistical opportunity presented itself, the occupiers and Quisling regime seized the opportunity to deport the Jews. Documents suggests that the government entered into this final phase without coordinating with Eichmann’s office in Berlin. Thus, this article argues that the initiative to destroy Norway’s Jews came from within, and was not the result of pressure from the German central authorities.